Bentonite/Ti(IV) as a natural based nano-catalyst for synthesis of pyrimido[2,1-b]benzothiazole under grinding condition - Mina Keihanfar; Bi Bi Fatemeh Mirjalili; Abdolhamid Bamoniri (Scientific Reports)
Abstract A new natural-based catalyst named Bentonite/Ti(IV) was prepared and characterized by FT-IR, FESEM, TEM, TGA, EDS-MAP, XRD, BET, XRF, XPS and ICP- MS. An efficient and simple one-pot three-component synthesis of pyrimido[2,1-b]benzothiazole derivatives was carried out by the reaction of aldehyde, 2-aminobenzothiazole, and ethyl acetoacetate. In this research, Bentonite/Ti(IV) was used for the synthesis of PBT derivatives in 80 °C under solvent-free conditions by electrical mortar-heater. Solvent-free conditions, simplicity of operation, easy work-up and use of an eco-friendly catalyst are some of advantages of this protocol.